2011
DOI: 10.3390/ijms12031519
|View full text |Cite
|
Sign up to set email alerts
|

Zeranol Down-Regulates p53 Expression in Primary Cultured Human Breast Cancer Epithelial Cells through Epigenetic Modification

Abstract: Epidemiological studies have suggested that there are many risk factors associated with breast cancer. Silencing tumor suppressor genes through epigenetic alterations play critical roles in breast cancer initiation, promotion and progression. As a growth promoter, Zeranol (Z) has been approved by the FDA and is widely used to enhance the growth of beef cattle in the United States. However, the safety of Z use as a growth promoter is still under debate. In order to provide more evidence to clarify this critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…This report is consistent with an emerging scientific consensus on the importance of low-dose effects distinct from overt cytotoxicity at higher doses [3]. Another study found that zeranol increased the proliferation of cancerous human breast epithelial cells to a greater degree than normal cells and down-regulated expression of the tumor suppressor gene p53 [42]. Ex vivo studies of cells isolated from the tissues of rats and beef heifers implanted with zeranol have found that further exposure to zeranol in vitro increases cell proliferation, upregulates oncogenes (e.g., cyclin D1), and/or downregulates tumor suppressor genes (e.g., p53) relative to cells from tissues of untreated animals [43,44].…”
Section: Zeranolsupporting
confidence: 76%
“…This report is consistent with an emerging scientific consensus on the importance of low-dose effects distinct from overt cytotoxicity at higher doses [3]. Another study found that zeranol increased the proliferation of cancerous human breast epithelial cells to a greater degree than normal cells and down-regulated expression of the tumor suppressor gene p53 [42]. Ex vivo studies of cells isolated from the tissues of rats and beef heifers implanted with zeranol have found that further exposure to zeranol in vitro increases cell proliferation, upregulates oncogenes (e.g., cyclin D1), and/or downregulates tumor suppressor genes (e.g., p53) relative to cells from tissues of untreated animals [43,44].…”
Section: Zeranolsupporting
confidence: 76%
“…They are frequently mutated and altered in most human cancers including breast cancer [15][17], [38], [39]. Normal breast epithelial cells induce p53-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation for the similar changes observed in p53 and p16 that both are tumor suppressor genes involved in many important physiological processes such as cell cycle arrest, gene transcription, DNA repair and apoptosis. They are frequently mutated and altered in most human cancers including breast cancer [15] [17] , [38] , [39] . Normal breast epithelial cells induce p53-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And in normal MCF-7 human ER+ cell line, addition of the growth promoter, zeranol, led to stimulatory effects on cell growth. These results were driven, at least in part, by down-regulation of the tumor suppressor gene p53, a process that was accompanied by up-regulation of DNA-methyltransferase 1 [ 84 ].…”
Section: Introductionmentioning
confidence: 99%